Modelling and multi-objective optimisation of sustainable solar-biomass-based hydrogen and electricity co-supply hub using metaheuristic-TOPSIS approach - Goh, Qi Hao; Zhang, Lian; Ho, Yong Kuen; Chew, Irene Mei Leng (Energy conversion and management, 2023)
[Display omitted] •Green hydrogen production from biomass fermentation and solar-powered electrolysis.•Optimisation of HECH capacity configuration with supply–demand variations.•Optimal HECH exhibits a total annualised cost of USD 9.43 mil./yr.•Minimised probability of hydrogen and electricity supply loss to 0.188 and 0.328.•Concurrently reduced probability of potential waste energy generation to 0.09. The utilisation of biomass and solar energy for green hydrogen production offers potential benefits in reducing carbon emissions and enhancing energy security, aligning with global sustainability efforts. However, research is still limited in optimising hybrid renewable energy systems that leverage biomass and solar energy for a balanced co-supply of hydrogen and electricity in industrial settings. In addition, the identification of optimal capacity configurations for these systems can be challenging, due to supply–demand variations and conflicting design objectives. For the first time, we demonstrate the use of a two-stage multi-objective metaheuristic-Technique for Order of Preference by Similarity to Ideal Solutions (TOPSIS) method for the design of a solar-biomass-based hydrogen and electricity co-supply hub (HECH), based on the consideration of economic, supply stability, and waste energy generation aspects. Through a proposed case study in Felda Taib Andak, Malaysia, the best-compromised solution for capacity setup is successfully determined. Among the metaheuristics screened, the TOPSIS-assisted multi-objective mayfly algorithm (MMA) provides the most preferred capacity arrangement, minimising the total annualised cost (TAC) to USD 9.43 mil./yr and hydrogen and power supply probabilities (LHSP and LPSP) to 0.188 and 0.328, respectively. The MMA-TOPSIS approach also reduces the potential energy waste probability (PEWP) of HECH down to 0.09. The study also discusses the feasibility of battery and hydrogen storage during critical periods such as low and high biomass feed supplies. Overall, the outcomes of this research offer guidance to the engineers in optimising HECH designs, which sets the groundwork for low-carbon energy development in biomass-related industrial ecosystems.